Diagnostic DNA-Flow- vs. -Image-Cytometry in Effusion Cytology - Helma Motherby; Natalia Pomjanski; Mary Kube; Alexandra Boros; Thomas Heiden; Bernhard Tribukait; Alfred Böcking (Analytical Cellular Pathology)
Aims: To determine the sensitivity and specificity of flow‐ and image‐cytometry for the detection of DNA‐aneuploidy as a marker for malignant cells in effusions. Methods: 200 effusions (80 tumor cell‐positive, 74 negative and 46 cytologically equivocal) were stained with DAPI‐SR for DNA‐flow‐ and with Feulgen‐Pararosaniline for ‐image‐cytometry. They were measured using a PAS‐flow‐cytometer and an AutoCyte‐QUIC‐DNA‐workstation according to the ESACP consensus reports for DNA‐flow‐ and ‐image‐cytometry, respectively [7,23,29,49]. Results: Sensitivity of DNA‐aneuploidy for the identification of malignant cells was 32.1% for DNA‐flow‐ and 75.0% for ‐image‐cytometry, specificity of ‐euploidy in benign cells was 100.0% for both methods. Positive predictive value of DNA‐aneuploidy for the identification of malignant cells was 100.0% for both techniques, negative predictive value of DNA‐euploidy was 48.6% for DNA‐flow‐ and 72.0% for ‐image‐cytometry. Conclusions: Searching for DNA‐aneuploidy as a diagnostic marker for neoplastic cells in serous effusions image‐cytometry revealed superior sensitivity as compared with monoparametric flow cytometry.